Peran Guru Mengaji Dalam Meningkatkan Kemapuan Membaca Iqra Di Tpa Al- Furqan - Eko Nursalim; Zahrina Farizah Adiliani (CV. ITTC INDONESIA, 2024)
Learning to read Iqro among children is an important aspect of religious education, especially in understanding the Qur'an. This study aims to identify the factors that influence the effectiveness of learning to read Iqro among children. The method used in this study is a qualitative approach with interviews and observation as data collection techniques. The results show that the effectiveness of learning is influenced by several factors, including children's motivation, parental support, teaching methods used, and a conducive learning environment. Children who are highly motivated and receive active support from their parents show better progress in their Iqro reading skills. In addition, the use of varied and fun teaching methods, such as educational games and visual media, can increase children's interest and engagement in the learning process. The study also identified challenges teachers face, such as children with learning difficulties and lack of support from parents. These findings provide insights for teachers and parents in creating a better learning environment and supporting the development of children's Iqro reading skills. Thus, collaborative efforts between teachers, parents and the community are needed to improve the effectiveness of learning to read Iqro.